PENGARUH TINGKAT KONSUMSI DAN KECERNAAN BK, PK ITIK MOJOSARI YANG DIBERI PAKAN CAMPURAN KEONG SAWAH - logho, Emanuel; Supartini, Nonok; Santoso, Erik Priyo (Fakultas Pertanian, 2017)
This study aims to determine the best treatment combination in the Mojosari duck ration. The study used a complete randomized design on each treatment with 3 replications resulting in 21 Test Units. From the research result showed that the highest consumption was in the treatment of A0B2 equal to 57,071,50 gr that was mixture of feed material between rice paddy 25% and Bekatul 75% with highest average value at treatment A0B2 equal to 380,48 gr / head / day. In the consumption of Digestibility Dry matter with the highest value at treatment A0B1 of 248.31 gr / head / day and also the highest daily rate of digestion at treatment A0B0 is 100% control feed. The highest dry matter digestibility percentage in A0B0 treatment was 76.85%. Highest Raw Protein Protein Consumption in A0B3 treatment was 62,82 gr / cow / day while mean of highest Raw Protein digestion was treated A0B3 equal to 54,60 gr / cow / day and highest percentage of digestibility Protein was found in treatment A0B3 equal to 86,90%. So from each treatment of feed consumption, dry matter digestibility as well as the digestibility of Rough Protein gives a very real difference P